BTEX compounds leachates from cigarette butts into water environment: A primary study. (15th January 2021) - Dobaradaran, Sina; Schmidt, Torsten C.; Kaziur-Cegla, Wiebke; Jochmann, Maik A.
Abstract: Cigarette butts (CBs) are the most abundant types of litter in the environment and may contain toxic chemicals such as BTEX that pose serious risks to the water bodies and health of aquatic organisms. So far there is no systematic study on BTEX compounds (benzene, toluene, ethylbenzene, o-xylene, and p-xylene) leaching from CBs into water environments. In this work, the leaching concentrations of BTEX compounds in deionized water (DW) and river water (RW) samples were studied for the first time. The mean concentrations of benzene, toluene, ethylbenzene, p-xylene, and o-xylene at contact times of 15 min to 1 day in water samples ranged from 0.13 to 0.18, 0.39–0.9, 0.11–0.25, 0.12–0.38, and 0.09–0.19 μgL −1 respectively. Benzene, toluene, ethylbenzene, o-xylene and p-xylene were detected at all contact times in both DW and RW samples. There were no significant differences of the leachate levels of BTEX compounds between DW and RW samples. The highest and lowest mean concentration levels in both DW and RW samples were determined for toluene and o-xylene respectively. The time after smoking had a significant effect on BTEX levels in leachates. The concentration levels of benzene, toluene, ethylbenzene, o-xylene and p-xylene leachates in water samples, after only 15 min, were reduced by 100, 93, 70, 68, and 59 percent respectively. Our data revealed that leached concentrations of benzene did not exceed the Water Framework Directive (WFD) guidelines, but with regard to the amount of CBs littered each year and other toxic chemicals contents of CBs this can still be a threat for aquatic creatures and possibly humans as well. Further studies are needed to cover the knowledge gap on the toxic leachates from CBs into water systems. Graphical abstract: Image 1 Highlights: BTEX were detected at all contact times in all water samples. Toluene and o-xylene had the highest and lowest levels in leachates respectively. Time after smoking had a significant effect on BTEX levels in leachates. Leached level of benzene from the cigarette butts did not exceed the WFD guidelines. Abstract : BTEX compounds can easily leach from cigarette butts into water and time after smoking has a significant effect on BTEX levels in leachates.